Brand conceptualization for academic libraries: A grounded theory approach - Sahli, Farzane; Alidousti, Sirous (Malaysian Journal of Library and Information Science, 2024)
Marketing and branding are still regarded as aspects of the business world irrelevant to libraries. Understanding the impact of brand and its evolution on the success of academic libraries necessitates elucidating the meaning of brand and its contributions to libraries. The lack of a comprehensive definition of marketing and branding and their functions in Iranian libraries also confirms the idea that they are unnecessary in libraries and prevents libraries from moving in the right direction in marketing and branding. To this end, this study aimed to investigate the brand concept of academic libraries in Iran. This qualitative study employed the grounded theory (GT) methodology based on two of the three coding steps suggested by Strauss and Corbin (1998): “open coding” and “axial coding”. Twenty experts in fields such as branding, marketing, and librarianship, among others, were interviewed for data collection purposes. Out of these experts, nine were faculty members, three were researchers, and eight were library employees. Using the MAXQDA software, the content of the interviews was analyzed qualitatively. In addition, the academic library brand was also conceptualized with 12 dimensions, including brand identity, brand associations, brand awareness, brand imagery, brand compatibility, brand quality, brand credibility, brand superiority, brand security, brand excitement, behavioral loyalty, and attitudinal attachment. Therefore, it made sense for the brand to focus on providing its customers with the best possible library experience. This study is the first to define the brand concept for academic libraries in order to shed light on the concept and its significance in these libraries.